A Comprehensive Examination of Entropy Differences in Triangular Fuzzy Numbers under Arithmetic Operations - Wang, Tien-Chin (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2025)
This scholarly investigation is dedicated to scrutinizing the entropy distinctions inherent in the arithmetic operations involving pairs of Triangular Fuzzy Numbers (TFNs), concurrently delving into the intricate relationships between these TFNs. An additional objective is to address gaps in the exploration of Wang and Chiu [7]. Fourteen theorems categorically articulate the entropy variations arising from diverse arithmetic operations on two TFNs, accompanied by corresponding illustrative examples that rigorously substantiate the theoretical framework. A noteworthy revelation of this study is the observed escalation in the degrees of fuzziness following arithmetic operations.